RF heating experiment to verify the design process of graphite target at the RAON μSR facility - Jeong, Jae Young; Kim, Jae Chang; Pak, Kihong; Kim, Yong Hyun; Kim, Yong Kyun; Lee, Wonjun; Lee, Ju Hahn; Jang, Taek Jin (Nuclear engineering and technology, 2023)
The purpose of the target system for the muon spin rotation, relaxation, and resonance (μSR) facility at the Rare isotope Accelerator complex for ON-line experiments (RAON) is to induce the production of a significant number of surface muons in thermally stable experiments. The manufactured target system was installed at RAON in the Sindong area near Daejeon in 2021. The design was made conservatively with a sufficient margin of safety through ANSYS calculations; however, verification experiments had to be performed on the ANSYS calculations. Because the 600-MeV proton beam has not yet been provided, an alternative way to reproduce the calculation conditions was required. The radio frequency (RF) heating method, which has not yet been applied to the target verification experiment but has several advantages, was used. It was observed that the RF heating method has promise for testing the thermal stability of the target, and whether the target system design process was performed conservatively enough was verified by comparing the RF heating experiments with the ANSYS calculations.